2020
DOI: 10.3991/ijet.v15i01.11013
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating K-12 Teachers in Creating Apps by Visual Programming and Project-based Learning

Abstract: The use of apps in education has become popular in recent years with the development of technology. How to prepare K-12 teachers in creating apps for students learning is worth our attention. This paper presents how to ap-ply visual programming and project-based learning to facilitate K-12 teachers in creating apps. Seven K-12 teachers with less computer background partic-ipated in this study. Data source including (1) K-12 teachers’ project codes, (2) K-12 teachers’ questionnaire, (3) K-12 teachers’ inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
(45 reference statements)
0
14
0
3
Order By: Relevance
“…It stresses primarily on the learning activities rather than educator activities that focus on the activities of active learners in getting the direct experience "learning by doing" (Kızkapan & Bektaş, 2017). Also, the findings of some studies have shown that PjBL positively supports instructional so that it is recommended to apply in other subjects (Chiu, 2020;Maulana et al, 2019). The strategy syntax of PjBL consists of pre-project and post-project.…”
Section: Introductionmentioning
confidence: 99%
“…It stresses primarily on the learning activities rather than educator activities that focus on the activities of active learners in getting the direct experience "learning by doing" (Kızkapan & Bektaş, 2017). Also, the findings of some studies have shown that PjBL positively supports instructional so that it is recommended to apply in other subjects (Chiu, 2020;Maulana et al, 2019). The strategy syntax of PjBL consists of pre-project and post-project.…”
Section: Introductionmentioning
confidence: 99%
“…A definition of textual programming is that it is written and modified with the help of a text editor (Chen et al , 2019; Chiu, 2020). Many see this as the authentic way of programming and the approach has a more established connection to professional development than block programming tools (Garneli et al , 2015; Tsukamoto et al , 2016; Mladenović et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A common challenge in previous research is that textual programming is more complex and difficult to learn for novice programmers than other types of programming, such as block programming (Garneli et al , 2015; Tsukamoto et al , 2016; Lindberg et al , 2019; Chiu, 2020). In a study on introducing programming to primary school students, textual programming tool did not seem to score as high as the block programming tool in regards to student motivation (Tsukamoto et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing students with CT will also strengthen students' confidence in their ability to problem-solve. There are various approaches to cultivating CT, such as block-based programming and games design [13,14,15,16,17], educational robotics [18,19,20,21], e-learning [22], and board games [23,24]. From the survey, most students in this class had no prior experience with programming, and block-based programming is considered as an alternative to foster CT because text-based coding is not easy for beginners to start coding and the language syntax is a barrier for students to better understand CT concepts [25].…”
Section: Introductionmentioning
confidence: 99%